Simultaneous exposure to vinylcyclohexene and methylmercury in Drosophila melanogaster: biochemical and molecular analyses - Bruna Candia Piccoli; Ana Lúcia Anversa Segatto; Cláudia Sirlene Oliveira; Fernanda D'Avila da Silva; Michael Aschner; João Batista Teixeira da Rocha (BMC, 2019)
Abstract Background Exposure to vinylcyclohexene (VCH) and methylmercury (MeHg+) can induce oxidative stress and gene modulation. Several studies have been evaluating the effects of VCH and MeHg+, but little is known about interactive effects between them. This work aimed to assess the exposure and co-exposure effects of MeHg+ and VCH on oxidative stress and gene modulation in Drosophila melanogaster. Methods Reactive species production, glutathione S-transferase (GST) and acetylcholinesterase (AChE) activities were evaluated after exposure and co-exposure to VCH (1 mM) and MeHg+ (0.2 mM) for one or three days in the head and body (thorax and abdomen) of flies. The expression of genes related to redox state and inflammatory response was evaluated after exposure and co-exposure to VCH and MeHg+ for three days. Results Survival decreased only in flies co-exposed to VCH and MeHg+ for three days. All treatments increased total reactive species production after one day of exposure. However, no significant changes were observed in the head after three days of exposure. One day of exposure to VCH caused an increase in the head GST activity, whereas MeHg+ induced an increase after three days of exposure. Regarding the body, all treatments increased GST activity after one day of exposure, but only the flies exposed to MeHg+ presented an increase in GST activity after three days of exposure. Treatments did not alter AChE activity in the head. As for gene expression, there was a significant increase in the Relish transcription factor gene in the flies' body, but Nrf2, Keap1, Jafrac1, TrxR1, and NF-κβ were not altered. Conclusion The results suggest that exposure to VCH and MeHg+ induce oxidative stress and activation of an inflammatory response in fruit flies.